Fish Processing Facilities: New Challenge to Marine Biosecurity in Canada. Issue 4 (9th December 2013) - Price, M. H. H.; Morton, A.; Eriksson, J. G.; Volpe, J. P.
Abstract: The transmission of pathogens is a common consequence of animal food production. Marine salmon farms and their processing facilities can serve as sources of virulent fish pathogens; our study is the first to confirm the broadcast of a live fish pathogen from a farmed salmon processing facility into the marine waters of Canada's Pacific coast. We found live salmon lice Lepeophtheirus salmonis, mucus, and fish tissue in effluent from the processing facility. Sea lice transmitted from this source may pose a threat to wild salmon populations, and the release of untreated offal, including blood water, is of considerable concern. Further research is needed to quantify the extent to which processing facilities release sea lice and to determine whether more virulent fish pathogens are present in effluent. These data underscore the need for fish farming nations to develop mandatory biosecurity programs to ensure that farmed salmon processing facilities will prevent the broadcast of infectious fish pathogens into wild fish habitat. Received April 26, 2012; accepted September 7, 2013